(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper presents a novel research study of the profit analysis regarding failure/repair rates of subunits of a Nippon Densan Corporation (NIDEC) Manufacturing Plant comprising of a various of subunits of varying manufacturing nature. In this paper behaviour and profit analysis of Nidec manufacturing plant are evaluated. The Nidec manufacturing plant contains six subsystems named as CNC machine (C), VMC machine (V), CNC hobbing machine (H), Induction hording machine (I), Grinding machine (G), and Polishing machine (P) so Nidec plant is a very complex system. All the subsystems are connected in series. A state transition diagram is developed using Markov process. The investigation of the system is completed by accepting that repair rates and failure rates are considered to be constant. The mathematical modeling is done by regenerative point graphical technique. The results are presented in the form of tables and graphs.